Application of concurrent grinding in direct aqueous carbonation of magnesium silicates. Issue 48 (June 2021) - Rashid, M.I; Benhelal, E.; Farhang, F.; Oliver, T.K.; Stockenhuber, M.; Kennedy, E.M.
Highlights: Concurrent grinding results six times higher magnesite yields. Concurrent grinding disintegrate silica-rich layers. Zirconia and stainless steel are better grinding media than alumina. Silica re-precipitation on grinding media observed. Dunite is more reactive compared to olivine and lizardite. Abstract: Formation of silica-rich passivation layers formed on the periphery of reacting feed particles is one of the primary obstacles in obtaining high magnesite yields during direct aqueous mineral carbonation of peridotites and serpentinites. The disruption of the silica-rich layer around partially reacted grains as a result of concurrent grinding on the degree of carbonation (magnesite yield) was investigated in this work. Three types of naturally-occurring magnesium silicate feedstocks, dunite, olivine and lizardite, as well as three types of grinding media, were examined. Discrete size fractions of feed samples, with and without grinding media, were carbonated. SEM readily disclosed the formation of a silica-rich shell around a magnesium rich core during carbonation. EDS analysis was employed to study the elemental composition of reacted particles' shell and core. The method confirmed that during concurrent grinding these silica-rich layers were removed and continuously produced a fresh surface available for further reaction. The removal of the silica-rich layer was shown to significantly improve magnesite yields up to a 600 % increase in yield. Among the three different grinding media used in this work, zirconia and stainless steel media resulted in similar and highest magnesite yields, which is believed to be due to a combination of their high densities and hardness. The findings of this research showed that enhanced magnesite yields could be achieved for all feedstock without the need for energy intensive pre-treatment steps ( e.g. ultrafine grinding and heat-activation). Moreover, concurrent grinding resulted in a magnesite yield when raw lizardite was carbonated.